Biochemistry of Sleep Quality and Daytime Sleepiness for Employees and University Students: Biokimia Kualitas Tidur dan Rasa Kantuk di Siang Hari untuk Karyawan dan Mahasiswa - Yunus, Tadamoun Sabah (Indonesian Journal on Health Science and Medicine, 2025)
Background: In the brain, neurotransmitters and hormones interact intricately to control sleep. While adenosine builds up over time to cause tiredness, neurotransmitters like serotonin and norepinephrine encourage wakefulness. Objectives: Measuring the impact of a lack of sleep on daytime sleepiness and daily performance and identifying factors affecting sleep, such as psychological stress, working hours, and daily habits. Methods: This study employs a descriptive, analytical, cross-sectional design. To measure daytime sleepiness and sleep quality, 150 college students were given a self-administered questionnaire. Data on sleep habits and their relationships can be gathered at a single point in time according to the study's cross-sectional design. Descriptive and inferential statistics were utilized to examine the replies, and convenience sampling was employed. Results: Based on the overall statistical results, which include the descriptive statistics for the mean score of 1.52 and a standard deviation of 0.175, the final assessment of sleep quality for individuals is classified as "Bad" This indicates that the majority of participants are experiencing poor sleep quality, as reflected by the mean score falling within the "Bad" range. Conclusion: This indicates that the majority of participants are experiencing poor sleep quality, as reflected by the mean score falling within the Bad range. Highlights: Neurotransmitters and hormones regulate sleep and wakefulness in the brain. Cross-sectional survey of 150 students using descriptive, inferential statistics. Most participants showed poor sleep quality with high daytime sleepiness. Keywords: Biochemistry, Sleep Quality, Daytime Sleepiness, Employees, University Students